Characteristics of gas generation from the pyrolysis of crude oil under the different geological conditions. (17th December 2018) - Huang, Yuxin; Hu, Wangshui; Sun, Yuanhui; Li, Zhongcheng; Zeng, Fancheng
Abstract: In order to investigate the gas generation from the pyrolysis of the crude oil, the thermal pyrolysis simulation experiment of the crude oil under the different geological conditions are carried out by using high temperature and high pressure closed system. The cumulative amounts of gaseous hydrocarbons from the pyrolysis of crude oil are almost the same but the generating activation energy are different under the different media (limestone, mudstone, sandstone). The limestone has the greatest impact on the pyrolysis, followed by the mudstone and the sandstone. In addition, pressure and heating rate have an inhibitory effect on the pyrolysis of crude oil. The experimental results can provide an evidence for source judgment and resource evaluation of natural gas in marine strata in China.